Optimizing windrow method vermicomposting practices for enhancing income generating of formers in Mahrajganj District of Uttar Pradesh: “ A Research Perspective.” - Abhishek Govind Rao; D.P. Singh; Vijay Chandra (Public Health, 2026)
Vermicomposting is an ecofriendly biological process involving the joint action of earthworms and mesophilic microorganism for the bio-oxidation and stabilization of organic wastes into nutrient rich vertices. The process effectively converts agricultural residues and cattle dung into high quality organic fertilizer while reducing waste volume by 40-60 per cent. Vermicompost is widely recognized as a valuable bio-fertilizer due to its balanced nutrient composition, rich microbial population and positive effects on soil physical, chemical and biological properties. The present study was conducted into two villages, namely Nandana and Pakadiyar Bishunpur of Maharajganj district, Uttar Pradesh, with the objective of optimizing windrow method vermicomposting practices for income generation among farmers. Thirty farmers were initially trained on various aspects of Vermicompost production, out of which eight interested farmers were selected for practical Vermicompost production under front line demonstration (FLD), socio- economic data of the respondents were collected prior to the intervention. Training on windrow method vermicomposting technology was imparted and farmer’s knowledge levels were assessed before and after the training programme. Under FLD, windrows of size 12 X 4 X 2 feet were prepared and 56 kg of Eisenia foetida earthworms were provided to each beneficiary. Result revealed that farmers had a low level of knowledge regarding vermicomposting practices before training, which increased significantly to nearly 98 % after training. The average production of Vermicompost and earthworms per six months (two cycles) was recorded as 2.27 tones and 20 kg, respectively. The activity generated an average gross income of Rs. 28,750.00 with a benefit- cost ratio of 7.32, indicating high profitability. The study clearly demonstrates that optimizing windrow method vermicomposting supported by capacity building and technical guidance can generating enterprises for small and marginal farmers.